2022
DOI: 10.1111/epi.17481
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, longitudinal, multicenter study on the provision of information regarding sudden unexpected death in epilepsy to adults with epilepsy

Abstract: Objective: Despite increased awareness of the serious epilepsy complication sudden unexpected death in epilepsy (SUDEP), a substantial population of people with epilepsy (PWE) remain poorly informed. Physicians indicate concern that SUDEP information may adversely affect patients' health and quality of life. We examined SUDEP awareness and the immediate and long-term effects of providing SUDEP information to PWE.Methods: Baseline knowledge and behaviors among PWE and behavioral adjustments following the provis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…18,27,29,30 In recent studies, >80% to 100% of PWEs and their caregivers have indicated the right to be informed about SUDEP. 31,32 Although PWEs recognize that discussing SUDEP may be alarming or frightening when receiving a diagnosis, this is usually short-lived. 33 When SUDEP is not discussed with PWEs and their caregivers, there is the potential that information may be sought from other sources, which can result in misinformation and anxiety.…”
Section: Methods Of Counselingmentioning
confidence: 99%
See 4 more Smart Citations
“…18,27,29,30 In recent studies, >80% to 100% of PWEs and their caregivers have indicated the right to be informed about SUDEP. 31,32 Although PWEs recognize that discussing SUDEP may be alarming or frightening when receiving a diagnosis, this is usually short-lived. 33 When SUDEP is not discussed with PWEs and their caregivers, there is the potential that information may be sought from other sources, which can result in misinformation and anxiety.…”
Section: Methods Of Counselingmentioning
confidence: 99%
“…30 Moreover, in a recent study in adults on the long-term impacts of learning about SUDEP, one-fourth of participants indicated that they had made substantial behavioral adjustments 3 months after learning about SUDEP. 31 Despite these findings, additional studies are needed to determine how counseling about SUDEP influences epilepsy selfmanagement and, ultimately, SUDEP risk. 37…”
Section: Methods Of Counselingmentioning
confidence: 99%
See 3 more Smart Citations